2012
DOI: 10.1111/cpsp.12004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying sexual violence exposure and psychosocial sequelae: A theoretical and empirical review.

Abstract: Sexual violence is associated with a range of negative mental health and behavioral sequelae, including posttraumatic stress disorder (PTSD), depression, substance abuse/dependence, risky sexual behavior, and interpersonal relationship problems. However, mechanisms underlying these associations are not well understood. Identifying mechanisms that explain linkages between sexual violence and poor outcomes is of paramount importance in determining when and how to intervene to prevent or reduce the magnitude of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 131 publications
(167 reference statements)
3
54
0
3
Order By: Relevance
“…Given that these common sequelae of assault are often theorized as mediators, this was surprising. However, it is possible that these factors are mediated by more proximal factors such as sexual refusal assertiveness, having more sexual partners, or problem drinking (Walsh, Galea, & Koenen, 2012). This is a likely explanation at least for maladaptive coping, which had the strongest bivariate correlations to almost all forms of revictimization in comparison with other predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that these common sequelae of assault are often theorized as mediators, this was surprising. However, it is possible that these factors are mediated by more proximal factors such as sexual refusal assertiveness, having more sexual partners, or problem drinking (Walsh, Galea, & Koenen, 2012). This is a likely explanation at least for maladaptive coping, which had the strongest bivariate correlations to almost all forms of revictimization in comparison with other predictors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, emotion dysregulation both mediates the path from betrayal traumas (such as interpersonal violence) to PTSD and the path from PTSD to substance use and sexual behaviors (Bonn-Miller, Vujanovic, Boden, & Gross, 2011; Goldsmith, Chesney, Heath, & Barlow, 2013; Weiss, Tull, & Gratz, 2014). Also, emotion dysregulation may increase compliance with sexual activity, impulsive behaviors, and maladaptive coping strategies, as well as decrease sexual refusal assertiveness, relationship stability, and the ability to use emotions as information to detect risk (Bonn-Miller et al, 2011; Cloitre & Rosenberg, 2006; Goldsmith et al, 2013; Marx, Heidt, & Gold, 2005; Messman-Moore, Walsh, & DiLillo, 2010; Orcutt et al, 2005; Walsh, DiLillo, & Messman-Moore, 2012;Walsh, Galea, & Koenen, 2012; Weiss et al, 2014; Zerubavel & Messman-Moore, 2013). Revictimized women report higher rates of emotion regulation difficulties (Walsh, DiLillo, & Scalora, 2011), and emotional dysregulation predicts revictimization (Messman-Moore et al, 2010; Messman-Moore, Ward, & Zerubavel, 2013; Messman-Moore, Ward, Zerubavel, Chandley, & Barton, 2015).…”
Section: Ontogenic Factorsmentioning
confidence: 99%
“…There is also evidence that a history of CSA may be associated with a greater likelihood of engaging in sexual risk behavior in adulthood (Meston, Heiman, & Trapnell, 1999;Parillo, Freeman, Collier, & Young, 2001;Testa, VanZile-Tamson, & Livingston, 2005;Van Bruggen, Runtz, & Kadlec, 2006). However, it should be noted that this relationship has not always been found (e.g., Hamburger et al, 2004;Littleton, Radecki Breitkopf, & Berenson, 2007;van Roode et al, 2009;Watson, Matheny, Gagne, Brack, & Ancis, 2013). Overall, the literature supports that having a CSA history is associated with engaging in sexual risk behavior during adolescence and may also be associated with the persistence of sexual risk behavior into adulthood.…”
mentioning
confidence: 99%
“…Systematic reviews of the adverse effects of childhood sexual abuse and sexual assault in adulthood reveal a broad constellation of psychological, behavioral, social, and physical health difficulties that negatively impact the lives of survivors (Bohn & Holz, 1996;Campbell, Dworkin, & Cabral, 2009;Jordan et al, 2010). PTSD, depression, anxiety, and substance abuse are among the most frequently reported mental health consequences and are often co-occurring (Chen & Ullman, 2010;Jordan et al, 2010;Kilpatrick, Resnick, Ruggiero, Conoscenti, & McCauley, 2007;Walsh, Galea, & Koenen, 2012). Voth Schrag and Edmond (2015) found that for RCC counselors reducing symptoms of anxiety, depression, and PTSD were among the most frequently endorsed treatment goals.…”
Section: Introductionmentioning
confidence: 99%